Antimicrobial Peptides and Chemicals Produced by Animals - Al-Baraa Akram; Glen McCann (Innovations in Microbiology and Biotechnology Vol. 5, 2022)
The problem of multidrug-resistant pathogens such as bacteria, fungus, and yeast, as well as the prohibition on using antibiotics as growth promoters in feed, has prompted researchers to seek for alternatives to traditional antibiotics, such as natural compounds with antibacterial action. Natural antimicrobial peptides and chemicals extracted from animal secretions and some insect venoms have sparked a lot of interest and research because they have antimicrobial activity against pathogens with lower resistance and higher synergistic effects when given in combination with blends of them. In this chapter, the use of yeast Saccharomyces cerevisiae to express antimicrobial peptides derived from honeybee venom will be addressed as well as antimicrobial chemicals extracted from giraffes with their inhibitory effects on liver microsomal enzymes CYP450 will be described also with its activity against microorganisms such as Agrobacterium rhizogenes, Aspergillus Niger, Candida albicans and E.coli using optical density analysis method then their minimum inhibitory concentrations (MIC) will be determined as well as ICs 50 to measure the potency to inhibit a biological function using programmes like Gene5, graph pad prism and clone manager as well as Antimicrobial action of compounds found in animal fluids is being investigated.